Cognitive fusion as a candidate psychological vulnerability factor for psychosis: An experimental study of acute ∆9-tetrahydrocannabinol (THC) intoxication. Issue 2 (3rd April 2021) - Newman-Taylor, Katherine; Richardson, Thomas; Lees, Rachel; Petrilli, Katherine; Bolderston, Helen; Hindocha, Chandni; Freeman, Tom P; Bloomfield, Michael A. P.
ABSTRACT: Heavy cannabis use is associated with an increased risk of psychosis. However, the psychological mechanisms involved, and interactions with established risk factors for cannabis-related psychosis, remain unclear. This study examined the role of cognitive fusion, a candidate vulnerability factor for psychosis, during acute THC intoxication, and the interaction with key risk factors – developmental trauma and schizotypy. Twenty general population cannabis-using participants were administered THC or placebo in a within-participants, double-blinded randomised study. Developmental trauma, schizotypy and cognitive fusion were all associated with psychotic experiences during intoxication. Cognitive fusion accounted for increased psychotic experiences in those with developmental trauma and high schizotypy. Cognitive fusion may be a key mechanism by which developmental trauma and schizotypy increase risk of psychosis from cannabis use. This initial study is limited by a small sample and correlational design; a larger scale mediation study is now needed to support a causal argument. The findings have implications for psychological treatments and identifying those at risk of cannabis-related psychosis. Psychological interventions that target cognitive fusion may be more effective than generic approaches. People prone to cognitive fusion, particularly those with a history of developmental trauma and high in schizotypy, may be at higher risk for cannabis-related psychosis.